Analysis The Element of the Gharar in The All You Can Eat System From The Perspective of Sharia Economic Law - Adelia, Nisa; MS, Habibah Lestari; Maulana, Akhmad; Rusdiyah; Rahmat Fadillah (Interdisciplinary Explorations in Research Journal, 2024)
Transactions in restaurants with the All You Can Eat system have attracted public attention because it gives customers freedom to take portions of food with a predetermined time limit and price. This study aims to analyse the element of gharar in the All You Can Eat system and provide insight into the legal issues and solutions related to this system. The research uses a qualitative method. The result is that there is an aspect of gharar in the All You Can Eat transaction system, and it reduces the validity of the transaction from the perspective of sharia economic law. To overcome this problem, the solutions that can be taken are improving the transparency aspect of menu presentation, determining reasonable consumption limits, implementing clear rules and regulations, and educating customers about the All You Can Eat concept and the responsibilities of using the system. In addition, restaurants can also consider a pre-set menu or meal plan system. This can reduce ambiguity in transactions and provide a more structured dining experience. Keywords: All You Can Eat, Sharia Economic Law, Gharar.